2010
DOI: 10.1038/mt.2009.232
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Efficacy of Vasculostatin (Vstat120) Expressing Oncolytic HSV-1

Abstract: Oncolytic viral therapy is a promising therapeutic modality for brain tumors. Vasculostatin (Vstat120), is the cleaved and secreted extracellular fragment of BAI1, a brain specific receptor. However, the therapeutic efficacy of Vstat120 delivery into established tumors has not been investigated. Here we tested therapeutic efficacy of combining Vstat120 gene delivery in conjunction with oncolytic viral therapy. We constructed a novel oncolytic virus RAMBO: Rapid Anti-angiogensis Mediated By Oncolytic virus, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 47 publications
2
91
0
1
Order By: Relevance
“…We also observed that oncolytic viral therapy with HF10 enhanced angiogenesis, possibly due to the inflammatory response induced by viral infection, and viral proteins expressed during viral replication. 30 The mechanisms underlying the enhanced inflammation are not precisely known, but preclinical data regarding herpetic stromal keratitis in wild-type HSV 1 infection revealed that angiogenesis may be induced by paracrine effects resulting from release of VP22 or the CpG motifs in the DNA of HSV 1, which are required for viral replication. [57][58][59][60] Most of these stimuli, especially the CpG motif, potently stimulate secretion of vascular endothelial growth factor (VEGF) A.…”
Section: X400 X400mentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that oncolytic viral therapy with HF10 enhanced angiogenesis, possibly due to the inflammatory response induced by viral infection, and viral proteins expressed during viral replication. 30 The mechanisms underlying the enhanced inflammation are not precisely known, but preclinical data regarding herpetic stromal keratitis in wild-type HSV 1 infection revealed that angiogenesis may be induced by paracrine effects resulting from release of VP22 or the CpG motifs in the DNA of HSV 1, which are required for viral replication. [57][58][59][60] Most of these stimuli, especially the CpG motif, potently stimulate secretion of vascular endothelial growth factor (VEGF) A.…”
Section: X400 X400mentioning
confidence: 99%
“…[27][28][29] There are many attempts to engineer viruses to express antiangiogenic molecules. [30][31][32] Also obscuring the true effect of oncolytic herpes viruses on angiogenesis is the fact that all data have been generated in animal models rather than clinical investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Human BAI1 expression is down-regulated in glioblastoma and is inversely correlated with neovascularization in colorectal and lung cancers, consistent with an antiangiogenesis function (20)(21)(22). The antiangiogenic activity of BAI1 is thought to be mediated by a fragment of its N-terminal extracellular sequence, a fragment known as vasculostatin (17,23,24). BAI2 and BAI3 expression are not p53-inducible, but both proteins also act as inhibitors of angiogenesis (11,14,15,25).…”
mentioning
confidence: 94%
“…163 Combining a lower dose of G47Δ-mAngio with a low (non-invasive) dose of bevacizumab further improved survival. 163 Expression of other naturally occurring angiogenesis inhibitors, vasculostatin and CXCL4 (PF4), have also been shown to improve the efficacy of oHSV in human glioma models 164,165 (Table III). IL-12, in addition to its immunostimulatory activity is also antiangiogenic in GSC-derived gliomas (Cheema T, Rabkin SD; unpublished results).…”
Section: Disrupting Tumor Microenvironmentmentioning
confidence: 99%
“…U87 [163] HSVQ-Vstat120 HSV Vstat120 Nude, i.c. U87DEGFR [164] G47Δ-PF4 HSV PF4 (CXCL4) Nude, s.c. U87 [165] Ad-isthmin RD-Ad Xenopus isthmin Nude, i.c. U251 [166] CRAdRGDflt-IL24 Ad mda7/IL-24 Nude i.c.…”
mentioning
confidence: 99%